2020
DOI: 10.3390/antibiotics9120878
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Appropriate Antibiotic Use in a Complex Intervention: Mixed-Methods Process Evaluation Alongside the Cluster-Randomized Trial ARena

Abstract: The cluster randomized trial ARena (sustainable reduction of antibiotic-induced antimicrobial resistance, 2017–2020) promoted appropriate use of antibiotics for acute non-complicated infections in primary care networks (PCNs) in Germany. A process evaluation assessed determinants of practice and explored factors associated with antibiotic prescribing patterns. This work describes its findings on uptake and impacts of the complex intervention program and indicates potential implementation into routine care. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
2
20
0
1
Order By: Relevance
“…Prescribing rates for quinolones were generally moderate to low in PCNs (9.9%) and RG (8.1%) and thus also match findings of the study from USA where in 9.4% of investigated visits for acute respiratory infections a broad-spectrum antibiotic was received [ 24 ]. Prescribing quinolones seemed to be associated with a higher number of comorbidities and higher patient age as well which complements findings of the process evaluation conducted alongside ARena where uncertainty about diagnoses, prognosis, continuity of care and perceptions about patient preferences were found to be among the reasons for non-indicated prescribing [ 25 , 26 ]. To some extend this confirms findings from a 2010 study that investigated fluoroquinolone prescribing for acute cough in German primary care to find predictors for unjustified prescribing.…”
Section: Discussionsupporting
confidence: 55%
“…Prescribing rates for quinolones were generally moderate to low in PCNs (9.9%) and RG (8.1%) and thus also match findings of the study from USA where in 9.4% of investigated visits for acute respiratory infections a broad-spectrum antibiotic was received [ 24 ]. Prescribing quinolones seemed to be associated with a higher number of comorbidities and higher patient age as well which complements findings of the process evaluation conducted alongside ARena where uncertainty about diagnoses, prognosis, continuity of care and perceptions about patient preferences were found to be among the reasons for non-indicated prescribing [ 25 , 26 ]. To some extend this confirms findings from a 2010 study that investigated fluoroquinolone prescribing for acute cough in German primary care to find predictors for unjustified prescribing.…”
Section: Discussionsupporting
confidence: 55%
“…This present study was based on survey data collected during the PE and the additional documentation (attendance data). Findings of qualitative analyses have been reported elsewhere [37][38][39]. Figure 2 summarizes the study design and sample size of the PE.…”
Section: Study Design Of the Process Evaluationmentioning
confidence: 88%
“…Findings in the PE conducted alongside ARena indicate that interviewed physicians did interpret additional compensation as one key to generate behavior change. However, additional compensation might only be an incentive to participate in a study, but of lesser importance after this decision is taken [39]. Jan et al [44] also identi ed increased administrative workloads and inadequate understandings of performance-based payment contents as principal reasons for aversions of family practitioners to engage.…”
Section: Discussionmentioning
confidence: 99%
“…Research further showed that PCNs can act as effective drivers of innovation and quality improvement, especially when communication and support functioned well within the networks [19,28,29]. Being part of a PCN can thus support the adoption of speci c behaviors and beliefs [13,19].…”
Section: Comparison To Previous Researchmentioning
confidence: 99%
“…When interpreting results, it should be considered that PCN member physicians might show stronger tendencies to innovation and development than physicians who are not part of a PCN [13,19]. The data analyzed in this study were generated in the process evaluation carried out alongside ARena.…”
Section: Comparison To Previous Researchmentioning
confidence: 99%